Biosmart and safe bus : new approach implementing epidemiologic triangle to reduce pathogen transmission on public transportation - Mentari, Alfitra Akbar Bara Mentari; Antari, Arlita Leniseptaria; Saraswati, Indah; Firmanti, Stefani Candra; Subagio, Agus; Prasetyo, Awal; Taufiq, Heydar Ruffa; Rowi, Khasan; Gufron, Ahmad (BKM Public Health and Community Medicine, 2024)
Background: Indirect pathogen transmission is one of the factors that cause the transmission of infectious problems from human to human. Surface cabine bus is one of the places that probably can be an intermediary of indirect pathogen transmission. Biosmart and Safe Bus is the concept of implementing an epidemiologic triangle, one of the innovations in Biosmart and Safe Bus is implementing silver nanoparticles as a coating in the cabine to decrease the bacterial load on the surface. Objective: To determine the effectiveness of coating silver nanoparticles in decreasing the bacterial surface load on the Biosmart and Safe Bus concept. Methods: This research used a post-test-only design with a control group. The sampling technique in this research is using surface swab sampling with a total of 18 samples in each Biosmart and Safe Bus and conventional bus that turn to Jakarta and Batu from Semarang. The data were analyzed by using the Mann-Whitney test, the Kruskal-Wallis test, and pairwise comparison Kruskal-Wallis test. Results: The results showed a significant difference between bacterial surface load on Biosmart and Safe Bus and conventional bus (p = 0.015). Along with it, the implementation of coating silver nanoparticles has a considerable effect (cohen effect size = 1.0324) in decreasing the bacterial surface load on the cabin of Biosmart and Safe Bus. The use of silver nanoparticles as a coating on the surface of Biosmart and Safe Bus is effective in being a surface antibacterial agent. This is in line with another research conducted in the United Kingdom with the result that the use of Ag antimicrobial BioCote as coating can reduce 95% surface bacteria. Conclusion: This research proved that coating silver nanoparticles is effective in decreasing the bacterial surface load on Biosmart and Safe Bus compared to a conventional bus.